If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9 = -5x + 7 Reorder the terms: -9 + 3x = -5x + 7 Reorder the terms: -9 + 3x = 7 + -5x Solving -9 + 3x = 7 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -9 + 3x + 5x = 7 + -5x + 5x Combine like terms: 3x + 5x = 8x -9 + 8x = 7 + -5x + 5x Combine like terms: -5x + 5x = 0 -9 + 8x = 7 + 0 -9 + 8x = 7 Add '9' to each side of the equation. -9 + 9 + 8x = 7 + 9 Combine like terms: -9 + 9 = 0 0 + 8x = 7 + 9 8x = 7 + 9 Combine like terms: 7 + 9 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| 4/60=p | | -5(x-7)=-5(2x+3) | | 66.8-2x=30 | | 3x^2-20=7 | | -2(g+5g)+-4(8f-(-12g))=equation | | 10a^3-18a^3= | | 1.2y+1.3y=0.64 | | 2t+12t-4(n+4n)=equation | | 9(2y+3)-12y=3 | | 5xy-12xy+12xy-9(x+y)=equation | | 5a-4-4a=6 | | 5x^2=-160+60x | | 11+.8x=5 | | -90=x+(-3) | | 3(2x-3)+7x=20 | | 5x-15=x+15 | | 2xy=8 | | 1/8(5/1x+4/1)=3/4 | | 12.7d-4.7d+8=6 | | 6b+8=56 | | 3x+x+4=8 | | 1/5(3/1r-4/1)=2/5 | | -2.8x=-56.0 | | 4x-65=19-2x | | 0.25=(x-179)/x | | 15=9p-8-8p | | 16t^2+12t=0 | | 19=-.875x+5 | | -0.5x+4=x+1.2 | | 12u^3+58u^2-84u= | | -6x-(-x+1)=9 | | p=2(20)+2(17) |